Efektifitas Terapi Sosial Skill Training pada Pasien dengan Isolasi Sosialdi Ruang Sub Akut Wanita RSKD Provinsi Maluku - Fitriyani Rumoga; Fany Sabban; Yerry Soumokil (Pusat Riset dan Inovasi Nasional, 2025)
Background: ocial Isolation is a condition of loneliness experienced by individuals and perceived as caused by others and as a negative and threatening condition. Therefore, patients who experience social isolation require social skills. One of the therapies that can be given to patients with social isolation is social skill training therapy. This therapy is used to improve a person's ability to express what is needed and desired, be able to reject and convey a problem, be able to provide a response during social interactions, be able to initiate interactions, be able to maintain interactions that are fostered to reduce anxiety, increase self-control in clients with social phobia and increase the client's ability in group activities.Objectives: improve individual communication skills and social skills for someone who experiences difficulties in interacting including problem-solving skills carried out and cooperating with other individuals, complaining about disapproval, giving praise, refusing requests from other individuals, according to the right to privacy, exchanging experiences with other individuals at the Maluku Provincial Hospital. Methods: The method used is a descriptive method in the form of a case study that identifies nursing care problems in social isolation patients, this study uses 1 patient as a sample. Results: In this scientific paper, a non-pharmacological intervention in the form of social therapy skill training was implemented on patients in social isolation for 3x8 hours so that the evaluation obtained was that the patient was able to socialize. Recommendation: It is hoped that families can apply social therapy skills training so that patients can continue to socialize.